THE REPRESENTATION OF SKINHEAD SUBCULTURE IN “THIS IS ENGLAND” MOVIE - Puji Lestari; Lambok Hermanto Sihombing (Universitas Muhammadiyah Gorontalo, 2022)
Movie sometimes constructs realities. We can see the way how people live, the way they think, and the way they dress through the movie. “This is England” is one of the movies that try to depict Skinhead subculture in England. In this study, the authors aim to analyze the representation of skinhead subculture taken from supporting scenes. To examine its representation, the authors applied qualitative approach by doing literature review. The authors utilized the elements of movie, Mise en Scene Theory from Manon de Reeper and Theory of Representation from Stuart Hall. As a result, this movie attempts to represent Skinhead community portrayed on the movie scenes.